The effect of immediate post-training active and passive recovery interventions on anaerobic performance and lower limb flexibility in professional soccer players - Rey, E.; Lago-Penas, C.; Casais, L.; Lago-Ballesteros, J. (Journal of Human Kinetics, 2012)
The capacity to recover from intense training, competition and matches is considered an important determinant in soccer performance. At present, there is no consensus on the effect of post -training recovery interventions on subsequent training session. The aim of this study was to determine the effectiveness of active (12 min submaximal running and 8 min of static stretching) and passive recovery (20 min sitting on a bench) interventions performed immediately after a training session on anaerobic performances (CMJ, 20 m sprint and Balsom agility test) and lower limb flexibility 24 h after the training. During two experimental sessions, 31 professional soccer players participated in a randomized fully controlled trial design. The first session was designed to evaluate the player`'s anaerobic performances and lower limb flexibility (pretest). After baseline measurements, participants performed a standardized soccer training during which heart rate and RPE were recorded to evaluate the training load. At the end of the training unit all players were randomly assigned to the active recovery group and the passive recovery group. A second experimental session was organized to obtain the posttest values. Players performed the same test, administered in the same order than in the first trial. No significant differences between groups were observed in heart rate and RPE. No significant effect due to recovery interventions was found on lower limb flexibility and anaerobic performances except CMJ that posttest value was significantly greater in the active recovery group than in the passive group (p < 0.05).